건강한 성인 남녀에서 Apolipoprotein A-Ⅰ 유전자 다형성과 혈중 지질농도와의 연관성 - 문재연; 박현영; 이종호; 이종은; 장양수; 조은영; 김원호; 최성훈; 고영국 (Korean circulation journal, 2004)
배경 및 목적： HDL 콜레스테롤의 구성 단백질인 Apolipoprotein (apo) A-Ⅰ의 유전자 다형성은 지질 대사에 영향을 미치는 것으로 알려져 있다. 본 연구는 심혈관계 질환이 없는 한국인 성인남녀에서 apo A-Ⅰ 유전자 다형성과 혈중 지질 농도 및 apo A-Ⅰ 농도와의 관련성을 분석하였다. 방 법： 417명의(남：여=169：248, 47.2±10.4세) 건강한 성인 남녀를 대상으로 본 연구를 진행하였다. apo A-Ⅰ유전자의 Xmnl 작용부위와 G-75A 유전자 다형성 분석은 단일염기확장(Single base extension) 방법의 SNPstream 25K system을 이용한 SNP-IT assay 방법으로 실시하였다. 결 과： Apo A-Ⅰ의 XmnI 제한효소 작용부위의 유전자다형성의 A 대립인자 발현빈도는 남자와 여자에서 각각 0.25, 0.23으로 서양인들의 0.12-0.14에 비해서 높았으며, G-75A 유전자 다형성의 A 대립인자의 빈도는 남자에서 0.19, 여자에서 0.17였고 두 유전자 다형성은 상호 강하게 연관되어 있었다(D’：0.990, p=0.004). 남성에서 XmnI 작용부위 유전자 다형성의 A대립인자군의 중성지방 농도는 128±71.1 mg/dL로 GG 유전형의 중성지방 농도 154±81.1 mg/dL보다 유의적으로 낮았으나(p=0.028), 여성에서는 통계적으로 유의한 차이가 없었다. 그러나 여성에서는 A대립인자군의 apoA-Ⅰ 농도는 GG 유전형에 비해 유의적으로 높았다. G-75A 유전자 다형성의 A대립인자군의 HDL 콜레스테롤 농도는 남녀모두에서 유전형에 따른 유의적인 차이는 없었다. 그러나 여성에서 A대립인자군의 apo A-Ⅰ 농도는 141.7±37.3 mg/dL으로 GG 유전형에 비해 유의적으로 높았다. 다중회귀분석결과 apo A-Ⅰ 유전자의 두 가지 유전자 다형성은 남성에서는 혈중 apo A-Ⅰ 농도와 유의한 관련이 없었으나 여성에서는 HDL 콜레스테롤 농도, 현재 흡연, XmnI 작용부위의 유전자 다형성의 A 대립인자는 apo A-Ⅰ 농도를 유의적으로 증가시키는 인자로 분석되었다. 결 론： 건강한 한국인 성인에서 Apo A-Ⅰ XmnI 작용부위 및 G-75A 유전자 다형성은 유전자 다형성은 남성에서는 중성지방농도와 여성에서는 apo A-Ⅰ농도와 유의한 관련성을 나타냈으며 이 두 유전자 다형성은 상호연관되어 있었다. Background and Objectives：Apolipoprotein A-I is the major lipoprotein constituent of high density lipoprotein in plasma. In this study, the role of two polymorphisms in the apo A-I gene was investigated on the serum lipid profiles and apo A-I levels in healthy men and women. Subjects and Methods：Blood samples were obtained from 417 subjects (M：F=169：248, mean age 47.2 years). The apo A-I genotypes were determined by SNP-IT assays using the SNPstream 25KTM system. Results：The frequencies of the A allele at the XmnI restriction site and position -75 bp were 0.25/0.23 and 0.19/0.17 in men and women, respectively. A strong positive linkage disequilibrium (D’=0.990) between two polymorphisms was detected. In men, the A allele at the XmnI restriction site was associated with significantly lower levels of triglyceride (p=0.028) compared to the G/G subjects, but no significant associations were detected between the G-75A polymorphism and any of the lipid traits examined. In women, each A allele for the XmnI restriction site and -75 bp polymorphisms were significantly associated with higher levels of apo A-I (p=0.032 and p=0.012). In the multiple regression analysis, the HDL, being a current drinker and the A allele of the XmnI restriction site polymorphism were major determinants of the serum apo A-I levels in women (R2=0.272, p<0.05). Conclusion：Our study showed that the A allele at XmnI restriction site in the apo A-I gene was associated with decreased triglyceride levels in men. Each A allele of two polymorphisms was associated with an elevated apo A-I level in women. KCI Citation Count: 2